Understand the uncoupling of tauopathy and dementia through comparative analysis of subgroups of atypical Alzheimer's disease patients. (December 2021) - Huang, Xiaoqing; Garfe, Nur Jury; Liu, Jiannan; Reeves, Cristian A Lasagna; Zhang, Jie
Abstract: Background: Typical Alzheimer's disease (AD) patient brains show characteristic neurofibrillary tangles (NFTs), which protein tau aggregates to form bundles of microtubule‐associated neurofibrillary tangle (NFT). A major focus of AD research has been the understanding of the roles of pathological tau in neurons and NFTs (tauopathy) in the disease initiation and progression, which severity can be measured with Braak staging. A subpopulation of patients also exist, whose brain showed typical AD‐like high NFTs, but with no or low cognitive deterioration (Asymptomatic AD or AsymAD) or present severe cognitive impairment but low NFTs (low‐NFT AD). Method: We performed differential expression analyses on both RNA and protein expression data from the atypical groups of MSBB and ROSMAP using typical AD patients as reference, then combined with pathway analysis to search for enriched pathway and upstream regulators which may play the neuron‐protective or neuron‐vulnerable role in the two atypical AD subgroups. Result: We identified oppositely regulated pathways as compared with typical AD group for the two atypical groups in MSBB cohort, such as oxidative phosphorylation pathway. Several enriched pathways related to immune response in the brain in the low‐NFT AD group are absent from AsymAD group. In ROSMAP cohort, we identified higher expression of actin‐binding proteins and ROS eliminating genes in AsymAD group, as well as higher expression of immune‐related proteins/mRNAs and PP1 regulatory genes/proteins in the low‐NFT AD group. Conclusion: Through the comparative analyses on transcriptomic and proteomic data, we identified several pathways/genes that may potentially render neuron‐protection or neuron‐vulnerability to AD for subgroups of atypical AD patients, including oppositely regulated oxidative phosphorylation and mitochondrial functions, elevated actin binding signals in AsymAD, and elevated inflammatory and PP1 regulatory signals in low‐NFT AD group. Further bioinformatic analysis will be performed to identify candidate genes/proteins and prioritize them for future in vivo animal model experiments. This work will not only improve precision medicine in AD, but also provide insights to prevent or slow down cognitive impairment during the long disease progression.